A melanocyte–melanoma precursor niche in sweat glands of volar skin. (4th September 2014) - Okamoto, Natsuko; Aoto, Takahiro; Uhara, Hisashi; Yamazaki, Satoshi; Akutsu, Hidenori; Umezawa, Akihiro; Nakauchi, Hiromitsu; Miyachi, Yoshiki; Saida, Toshiaki; Nishimura, Emi K.
Summary Determination of the niche for early‐stage cancer remains a challenging issue. Melanoma is an aggressive cancer of the melanocyte lineage. Early melanoma cells are often found in the epidermis around sweat ducts of human volar skin, and the skin pigmentation pattern is an early diagnostic sign of acral melanoma. However, the niche for melanoma precursors has not been determined yet. Here, we report that the secretory portion (SP) of eccrine sweat glands provide an anatomical niche for melanocyte–melanoma precursor cells. Using lineage‐tagged H2B‐GFP reporter mice, we found that melanoblasts that colonize sweat glands during development are maintained in an immature, slow‐cycling state but renew themselves in response to genomic stress and provide their differentiating progeny to the epidermis. FISH analysis of human acral melanoma expanding in the epidermis revealed that unpigmented melanoblasts with significant cyclin D1 gene amplification reside deep in the SP of particular sweat gland(s). These findings indicate that sweat glands maintain melanocyte–melanoma precursors in an immature state in the niche and explain the preferential distribution of early melanoma cells around sweat glands in human volar skin.